Investigating the Agricultural Applications of Acryl Amide based Hydrogel - Radwan, M. A.; Al-Sweasy, Omar; Sadek, M. A.; A. Elazab, Hany (International Journal of Engineering and Technology, 2018)
Hydrogel is classified as one of the most effective materials due to its widely used applications either in tissue or agriculture engineering. This scientific research aims to investigate the potential applications of hydrogels in the field of desert agriculture in dry places. In this research hydrogel was prepared under several conditions in order to evaluate and optimize the conditions. The research included optimizing several factors including cross-linking agent, water temperatures and pH. The potential agricultural applications of hydrogel were alsoÂ investigated.